2018
DOI: 10.1007/s10461-018-2241-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Extended-Release Naltrexone on HIV-Related and Drinking Outcomes Among HIV-Positive Patients: A Randomized-Controlled Trial

Abstract: We sought to test the efficacy of extended-release naltrexone (XR-NTX) on HIV-related and drinking outcomes. From April 2011-February 2015, we conducted a 4-site randomized double-blind placebo controlled clinical trial involving 51 HIV-positive patients with heavy drinking and < 95% antiretroviral (ART) adherence. All participants received counseling. The primary outcome was proportion with ≥ 95% ART adherence. Secondary outcomes included HIV biomarkers, VACS Index score, and past 30-day heavy drinking days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 61 publications
(83 reference statements)
0
32
0
Order By: Relevance
“…As shown in Table 1, two of these studies have used oral naltrexone (NTX) [44,49] and the 5 other used extendedrelease injectable form (XR-NTX) [45][46][47][48]50]. The difference between reported outcomes and a small number of studies has made it difficult to present results in a metaanalysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Table 1, two of these studies have used oral naltrexone (NTX) [44,49] and the 5 other used extendedrelease injectable form (XR-NTX) [45][46][47][48]50]. The difference between reported outcomes and a small number of studies has made it difficult to present results in a metaanalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 51 participants who enrolled in the study by Edelman et al, 2019, only 23 participants remained in the study for up to 24 weeks [45]. 82% of Cook et al, 2017 study participants completed the course of treatment [44].…”
Section: Evaluated Outcomes Treatment Retentionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most clinical trials involving naltrexone have only examined its effect on drinking, although reanalysis of at least one study one study demonstrated that reduction in drinking among clinical trial participants is accompanied by improvements in clinical health such as blood pressure, liver enzymes, and quality of life (Witkiewitz et al., ). Two recent studies sought to determine whether naltrexone or other alcohol‐related therapy can improve HIV outcomes, one of which found that reductions in drinking were associated with improved HIV viral suppression (Edelman et al., ; Springer et al., ).…”
Section: Discussionmentioning
confidence: 99%